DEFINING MUSTAHIQ: The Entangled Practice of Zakat and Religious Authority in Contemporary Madura, Indonesia - Wahed, Abdul (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2024)
This article deals with the Islamic legal reasoning behind the designation of Islamic religious leaders (kiai) in Madura as mustahiq zakat, highlighting the negotiation between fiqh, socio-political dynamics, and cultural interests in Indonesia’s evolving Muslim society. The kiai play a central role in both religious and socio-political domains. This article explores the justification for their eligibility to receive zakat and their responses to this designation. Employing a qualitative approach, data were collected through participant observation, in-depth interviews, and document analysis. The findings reveal that kiai have engaged in an internalization process by interpreting the category of fi sabilillah as a legal basis to include themselves as mustahiq zakat. Their interpretation is constructed through three strategies: externalization, objectification, and internalization. Furthermore, as holders of religious authority, kiai expand this interpretation to legitimize their right to zakat within a broader socio-religious framework.